Cytotoxic activity of non-specific lipid transfer protein (nsLTP1) from Ajwain (Trachyspermum ammi) seeds - Saud O. Alshammari; Taibah Aldakhil; Qamar A. Alshammari; David Salehi; Aftab Ahmed (BMC, 2022)
Abstract Background Trachyspermum ammi, commonly known as Ajwain, is a member of the Apiaceae family. It is a therapeutic herbal spice with diverse pharmacological properties, used in traditional medicine for various ailments. However, all previous studies were conducted using small molecule extracts, leaving the protein's bioactivity undiscovered. Aim The current study aimed to demonstrate the cytotoxic activity of Ajwain non-specific lipid transfer protein (nsLTP1) in normal breast (MCF10A), breast cancer (MCF-7), and pancreatic cancer (AsPC-1) cell lines. Also, to evaluate its structural stability in human serum as well as at high temperature conditions. Methods The cytotoxic activity of Ajwain nsLTP1 was evaluated in MCF-7 and AsPC-1 cell lines using MTT assay. Annexin V-FITC and PI staining were used to detect the early apoptotic and late apoptotic cells. The role of nsLTP1 in inducing apoptosis was further studied by quantifying Bcl-2, Bax, Caspase-3, Survivin, EGFR, and VEGF genes expression using RT-PCR. CD spectroscopy analyzed the nsLTP1 conformational changes after thermal treatment for structure stability determination. The RP-HPLC was used to analyze the nsLTP1 degradation rate in human serum at different time intervals incubated at 37 °C. Results Ajwain nsLTP1 showed a potent cytotoxic effect in MCF-7 and AsPC-1. The IC50 value obtained in MCF-7 was 8.21 μM, while for AsPC-1 4.17 μM. The effect of nsLTP1 on stimulating apoptosis revealed that the proportions of apoptotic cells in both cell lines were relatively increased depending on the concentration. The apoptotic cells percentage at 20 μM was in MCF-7 71% (***P < 0.001) and AsPC-1 88% (***P < 0.001). These results indicate that nsLTP1 might efficaciously induce apoptosis in multiple types of cancerous cells. Genes expression in MCF-7 and AsPC-1 showed significant upregulation in Bax and Caspase-3 and downregulation in Bcl-2, Survivin, EGFR, and VEGF protein. The CD analysis of nsLTP1 showed a significant thermostable property. In serum, nsLTP1 showed a slow degradation rate, indicating high stability with a half-life of ~ 8.4 h. Conclusion Our results revealed the potential anticancer activity of Ajwain nsLTP1 and its mechanism in inducing apoptosis. It further exhibited thermostable properties at high temperatures and in human serum, which suggested this protein as a promising anticancer agent.